Longitudinal analysis of reporting and quality of systematic reviews in high‐impact surgical journals. Issue 3 (21st December 2016) - Chapman, S. J.; Drake, T. M.; Bolton, W. S.; Barnard, J.; Bhangu, A.
Abstract: Background: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) Statement aims to optimize the reporting of systematic reviews. The performance of the PRISMA Statement in improving the reporting and quality of surgical systematic reviews remains unclear. Methods: Systematic reviews published in five high‐impact surgical journals between 2007 and 2015 were identified from online archives. Manuscripts blinded to journal, publication year and authorship were assessed according to 27 reporting criteria described by the PRISMA Statement and scored using a validated quality appraisal tool (AMSTAR, Assessing the Methodological Quality of Systematic Reviews). Comparisons were made between studies published before (2007–2009) and after (2011–2015) its introduction. The relationship between reporting and study quality was measured using Spearman's rank test. Results: Of 281 eligible manuscripts, 80 were published before the PRISMA Statement and 201 afterwards. Most manuscripts (208) included a meta‐analysis, with the remainder comprising a systematic review only. There was no meaningful change in median compliance with the PRISMA Statement (19 (i.q.r. 16–21) of 27 items before versus 19 (17–22) of 27 after introduction of PRISMA) despite achieving statistical significance ( P = 0·042). Better reporting compliance was associated with higher methodological quality ( r s = 0·70, P < 0·001). Conclusion: The PRISMA Statement has had minimal impact on the reporting of surgical systematic reviews. Better compliance was associated with higher‐quality methodology. Abstract : Authors and journals both need to do better